Factors and Material Conditions for Space-Intensive Economic Development of Region - Morkovkin, Dmitry E.; Mamychev, Alexei Y.; Yakovenko, Nataliya V.; Komov, Igor V.; Derevyagina, Mariya V.; Didenko, Olga V. (International Review of Management and Marketing, 2016)
The strategic goal of Russia - 2020 is to change the economic model of the country with the raw material for innovation, improving the efficiency of government and a sharp improvement in the quality of life of Russians. New target settings defined in the strategy, focus on quality rather than quantitative results of forcing a new look at content management at all hierarchical levels: federal, regional, territorial. In economic studies last 30-40 years there has been increasing interest in the economic side of the speakers at the regional level. This reflects the objective processes of globalization of the economy, which began to play a special role of spatial and economic “point” of the industrial and innovative development. In turn, the existence and the functioning of such “points” in the national economy in a certain way affect the inter-regional mobility of factors of production, which has a direct impact on regional economic performance, in both quantitative and qualitative aspects. Keywords: regional economics, economic space, production, development JEL Classifications: C40; P25